The Mixtec Pictorial Manuscripts Time, Agency and Memory in Ancient Mexico - Jansen, Maarten (The Early Americas: History and Culture, 2010)
This handbook surveys and describes the illustrated Mixtec manuscripts that survive in Europe, the United States and Mexico.